Special Aspects of Nuclear Energy as Object to Control - M. V. Golovko; Yu. V. Vertakova; V. Y. Galkovskaya; A. N. Setrakov (Глобальная ядерная безопасность, 2022)
This article examines the special aspects of nuclear energy as an object to control. The article provides normative legal acts regulating this process, and conclusions on the directions of their improvement. Such a feature of nuclear power facilities as the cost of construction and operation projects, as well as the need to ensure safety in strict accordance with the current standards, distinguishing them from other business entities, is noted. The experience of the application of the mechanism of public-private partnership and its role in the formation of the competitive position of the State Atomic Energy Corporation «Rosatom» in the market of developing countries is considered.